Evaluating the Efficiency of Budget Process in Ukraine - Denysiuk Oleksandr V. (Bìznes Inform, 2019)
The article is aimed at allocating the constituents of the characteristics of «efficiency of budget process» and identifying deformations of the budget process in Ukraine. The definition of «efficiency of budget process» is provided. The constituents of the efficiency of the budget process are grouped by the principle of universality for the stages of the budget process in the general ones (those that are peculiar to all stages of the budget process) and the specific ones (those that characterize only a separate stage of budget process). The following deformations of the budget process in Ukraine are allocated: delays in submission, consideration of projects and approval of the Law on the State Budget of Ukraine (decisions on local budget); insufficient level of transparency of process and low activity of the public in formation of budgetary decisions; systematicity of the most violations of the budget legislation; lack of accuracy of forecasts of both the macroeconomic and the budget indicators.